Consideration of Mandibular Third Molar Extraction for Post-Orthodontic Relapse Prevention - Narmada, Ida Bagus; Alida, Alida; Primadewi, Theresia (Faculty of Dental Medicine Universitas Airlangga, 2022)
Background: Orthodontic treatment may result in undesired teeth movement which is called